FRI0558 Predictors of mortality and re-fracture at 1 and 3years after hip fracture. (15th June 2017) - Brites, L; Marques, M; Daniel, A; Santiago, M; Marques, A; Silva, J Pereira da
Abstract : Background: Osteoporosis is a major health problem, particularly in the elderly, because of fragility fractures and their consequences. Hip fractures (HF) are the most ominous in terms of morbi-mortality. Objectives: The aim of our work was to establish the current mortality and re-fracture rate at 1 and 3 years after HF, as well as their predictors. Methods: The study included all patients aged >40 years, admitted to Coimbra University Hospital between May and October 2013 with the diagnosis of HF. Demographic and clinical data related to the fracture episode was collected from medical files. Patients or the caregiver were contacted to assess potential risk factors at baseline and major post-fracture events at 1 and 3 years after the index HF. The mortality and re-fracture rate 1 and 3 years after fracture were calculated. Possible predictor variables were tested by cox regression analysis: age, gender, physiotherapy, number of re-fractures, BMI, parent hip fracture, current smoking, corticotherapy, rheumatoid arthritis, secondary osteoporosis, alcohol, history of falls, anti-osteoporotic treatment, Katz index of independence in activities of daily living and Charlson comorbidity index. All FRAX® variables were defined as established in this algorithm. Results: A total of 130 patients satisfied the inclusion criteria, with a mean age of 82±8, 7 years, 69% being female). Mortality rates were of 30% and 41% at 1 and 3 years after HF respectively (Fig.1 ). Age, physiotherapy, parent fractured hip, corticotherapy, alcohol consumption (>3/day) and Charlson índex were statistically significant predictors of mortality at 3 years in multivariable analysis (Tab.1). Re-fracture rates at 1 and 3 years after the index fracture was 3, 8% and 11% respectively (Fig.1 ). We were unable to identify any statistically significant predictors of re-fracture. Conclusions: We concluded that HF have a great impact on the older population, leading to high morbidity and mortality. In our study, age, physiotherapy, parent hip fracture, corticotherapy, alcohol consumption and Charlson índex are related with increasing mortality in patients who suffered a fagility HF. Disclosure of Interest: None declared